CDK5RAP2 primary microcephaly is associated with hypothalamic, retinal and cochlear developmental defects. Issue 6 (3rd February 2020) - Nasser, Hala; Vera, Liza; Elmaleh-Bergès, Monique; Steindl, Katharina; Letard, Pascaline; Teissier, Natacha; Ernault, Anais; Guimiot, Fabien; Afenjar, Alexandra; Moutard, Marie Laure; Héron, Delphine; Alembik, Yves; et al.
Abstract : Background: Primary hereditary microcephaly (MCPH) comprises a large group of autosomal recessive disorders mainly affecting cortical development and resulting in a congenital impairment of brain growth. Despite the identification of >25 causal genes so far, it remains a challenge to distinguish between different MCPH forms at the clinical level. Methods: 7 patients with newly identified mutations in CDK5RAP2 (MCPH3) were investigated by performing prospective, extensive and systematic clinical, MRI, psychomotor, neurosensory and cognitive examinations under similar conditions. Results: All patients displayed neurosensory defects in addition to microcephaly. Small cochlea with incomplete partition type II was found in all cases and was associated with progressive deafness in 4 of them. Furthermore, the CDK5RAP2 protein was specifically identified in the developing cochlea from human fetal tissues. Microphthalmia was also present in all patients along with retinal pigmentation changes and lipofuscin deposits. Finally, hypothalamic anomalies consisting of interhypothalamic adhesions, a congenital midline defect usually associated with holoprosencephaly, was detected in 5 cases. Conclusion: This is the first report indicating that CDK5RAP2 not only governs brain size but also plays a role in ocular and cochlear development and is necessary for hypothalamic nuclear separation at the midline. Our data indicate that CDK5RAP2 should be considered as a potential gene associated with deafness and forme fruste of holoprosencephaly. These children should be given neurosensory follow-up to prevent additional comorbidities and allow them reaching their full educational potential. Trial registration number: NCT01565005 .